Transforming Teaching Practices: The Impact of ICT-Infused Professional Development Workshops - A Case Study - Ramulumo, Moleboheng; Mphuthi, Gabriel; Puleng, Rankweteke; Mazibe, Ernest; Mukhati, Fulufhelo (International Journal of Research in STEM Education, 2024)
This study examines the effectiveness of Information and Communication Technology (ICT)-infused Teacher Professional Development (TPD) workshops in enhancing teaching practices and learning experiences within the Technological Pedagogical Content Knowledge (TPACK) framework. A qualitative research design was adopted to capture the experiences of a single teacher participant involved in these workshops. Findings from thematic analyses of interviews and observational data indicate that the workshops significantly improved teaching practices by aligning them with Bloom’s taxonomy and effectively addressing diverse student needs. However, the study revealed a lack of significant change in retention of electricity formulae among students, suggesting the need for varied instructional strategies. The study recommends broader incorporation of diverse teaching methodologies to meet evolving educational demands and to enhance effectiveness in STEM education. Despite its insights, the research calls for further investigation with a larger sample to better understand the widespread impact of ICT-infused TPD workshops across different educational settings.